European Innovation Dynamics and US Economic Impact: Theory and Empirical Analysis - Paul J. J. Welfens; Tony Irawan (Institute for the Study of Labor (IZA), 2014)
The role of product innovations is growing in the world economy, and the EU and the US are key players here. The analysis presented herein explains product innovations in the EU25 for the period 2006-2012, namely through lagged R&D (relative to GDP), cumulated FDI inflows (relative to the host country capital stock) and cumulated FDI inflows (relative to the host country capital stock), joint internet intensity, broadband intensity and potential competition. For the first time we can offer a broad analysis of product innovation dynamics in Europe which should be the basis for not only better supply-side policy in EU countries and growth policy, respectively, but it also suggests a strong role for international digital communication in relation to product innovation dynamics. Moreover, the approach provides new important arguments in favor of the TTIP negotiations between the US and the EU and it suggests a broader analytical link between trade, FDI, innovation, employment and output growth.
Keywords: F21; F15; O31; 330; innovation; foreign direct investment; TTIP negotiation